2022
DOI: 10.1038/s41593-022-01170-x
|View full text |Cite|
|
Sign up to set email alerts
|

Oligodendrocyte precursor cells engulf synapses during circuit remodeling in mice

Abstract: Oligodendrocyte precursor cells (OPCs) give rise to myelinating oligodendrocytes throughout life, but the functions of OPCs are not limited to oligodendrogenesis. Here we show that OPCs contribute to thalamocortical presynapse elimination in the developing and adult mouse visual cortex. OPC-mediated synapse engulfment increases in response to sensory experience during neural circuit refinement. Our data suggest that OPCs may regulate synaptic connectivity in the brain independently of oligodendrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 24 publications
(33 reference statements)
0
40
0
Order By: Relevance
“…One should recognize that synaptic transmission is no longer unique to neurons but also involves mutual crosstalk between glial cells and neurons at the synaptic level in the control of brain functions. Recently, Auguste et al reported that OPCs engulf thalamocortical synapses in the developing and adult mouse visual cortex and that such OPC‐mediated synapse elimination is beneficial to sensory experience during neural circuit refinement, indicating that diverse functions of OPCs are constantly being revealed (Auguste et al, 2022). Thus, glia, as indispensable neural cells in the brain, play crucial roles in neuronal circuitry and actively modulate synaptic transmission under both physiological and pathological conditions including, among many others, neurodegenerative, mood, and memory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…One should recognize that synaptic transmission is no longer unique to neurons but also involves mutual crosstalk between glial cells and neurons at the synaptic level in the control of brain functions. Recently, Auguste et al reported that OPCs engulf thalamocortical synapses in the developing and adult mouse visual cortex and that such OPC‐mediated synapse elimination is beneficial to sensory experience during neural circuit refinement, indicating that diverse functions of OPCs are constantly being revealed (Auguste et al, 2022). Thus, glia, as indispensable neural cells in the brain, play crucial roles in neuronal circuitry and actively modulate synaptic transmission under both physiological and pathological conditions including, among many others, neurodegenerative, mood, and memory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, or in addition, enhanced OLP proliferation and the consequent increase in OLP population density, which persisted for at least 2 weeks post-training in the white matter, might itself lead to improved cognitive performance. There are reports that immature OL lineage cells in zebrafish (Marisca et al, 2020;Xiao et al, 2022) and mice (Buchanan et al, 2021;Auguste et al, 2022) can exert effects on neurons that are unrelated to myelination, including synaptic pruning by OLPs (Buchanan et al, 2021;Auguste et al, 2022). It is conceivable that such non-canonical effects could have a lasting impact on neural circuitry even if the responsible OL lineage cells are eventually eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Both NPCs and OPCs can also act as phagocytes. Dcx + (Doublecortin) neuroblasts, which are derived from NPCs and represent committed proliferative progenitors that are destined to differentiate into neurons, phagocytose dead neurons, whereas OPCs can phagocytose myelin debris and prune synapses; properties typically attributed to microglia and macrophages (Lu et al, 2011;Falcão et al, 2018;Auguste et al, 2022). NPCs and OPCs also directly react to frontiersin.org de Almeida et al 10.3389/fncel.2023.1130205 neuroinflammatory environment through chemokine and cytokine receptors that they express, and actively participate in modulating the inflammatory environment by secreting chemokines and cytokines (Watson et al, 2020(Watson et al, , 2021Belenguer et al, 2021;Shariq et al, 2021;Willis et al, 2022;Dittmann et al, 2023).…”
Section: "Immune" Roles Of Npcs In Cns Development and Regenerationmentioning
confidence: 99%